KAJIAN PENGHIDUPAN (LIVELIHOOD) MASYARAKAT AKIBAT BANJIR LAHAR HUJAN KALIPUTIH DI DESA SIRAHAN KECAMATAN SALAM KABUPATEN MAGELANG - , RINDU ALAM RINJANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The change in living conditions is the one of the effects of the disaster. The purpose of this study to determine the post-disaster living conditions, the level of community disaster resilience as well as whether there is influence between the living conditions of the resilience level. This study uses a combination of quantitative and qualitative (mixed methods) with a research instrument in the form of a questionnaire with a sample size of 93 people. Results Data were analyzed using multiple regression analysis with the independent variables are the living conditions and the dependent variable was resilience. This study uses some assumptions of classical test covering multi co- linearity Test, hetero-cedastity test, t test, and the test f. The results showed that post-disaster livelihoods conditions changes. Conditions asset decreased exception of human capital is getting looks good, this is due to the disaster, people increasingly seek and optimize existing resources. Post-disaster community resilience level is at medium and high levels, there is no community in each village with low resilience, the condition can occur due to factors associated with the psychological resilience so that there are factors within the individual comes from the individual's own different. Livelihood conditions affect the level resilience, changes in each asset based on the regression coefficients of each variable X to variable Y can be detailed as follows. Human capital effect of 0.541 to resilience, social capital amounted to 0,580, the natural capital of 0.567, 0.759 physical capital, financial capital of 0.53, and the activity was 0.417 with a coefficient of 2.707 means that if X1, X2, X3, X4, X5, X6 is 0% then the resilience of 2.707%.